Usmerjanje trajnostnega razvoja podjetja - Štrukelj, Tjaša; Rožman, Maja (2025)
Guiding Sustainable Business Development. The publication Guiding Sustainable Business Development explores the significance of sustainable development as a cornerstone of modern business operations. It presents the 17 Sustainable Development Goals (SDGs) and emphasizes their integration into business models to enhance competitiveness, resilience, and long-term success. The publication examines innovative business models, the impact of sustainability legislation, and the inclusion of social responsibility and diversity in corporate strategies. Special attention is given to the sustainable (re)orientation of family businesses and the role of non-profit organizations. It offers theoretical foundations, analyses of best practices, and concrete examples of sustainable management and innovation. The aim is to raise awareness of the importance of sustainable development, promote new approaches in business practices, and foster collaboration between businesses, the academic community, and society. This contribution supports the creation of a sustainable future and ensures the long-term success of companies in a dynamic global environment.
Keywords: sustainable development; sustainable governance and management; sustainable business strategies; corporate social responsibility; innovative business models